2011
DOI: 10.1007/s10620-011-1869-6
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Interferon Used to Treat Prior Partial-Responders to Pegylated Interferon Plus Ribavirin

Abstract: The use of c-IFN plus ribavirin in the retreatment of prior peg-IFN plus ribavirin partial responders is essentially twice that achieved in prior re-treatment regimens consisting of a second course of peg-IFN plus ribavirin. These results will need to be evaluated against the use of triple therapy consisting of a peg-IFN plus ribavirin and a protease inhibitor. More studies utilizing c-IFN plus ribavirin with either a protease inhibitor or polymerase inhibitor need to be performed as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The approved dose of CIFN varies from country to country; for instance, in the United States, the approved dose is 15 μg three times a week given subcutaneously, whereas in Germany it is 9 µg three times a week (3, 17, 32). To provide more favorable kinetics and subsequent maximal viral suppression, a daily dosing trial was attempted (17, 33, 34). However, in DIRECT trial, a daily dose of 15 µg was found to be associated with discontinuation of CIFN in 21% patients due to various side effects (33).…”
Section: Discussionmentioning
confidence: 99%
“…The approved dose of CIFN varies from country to country; for instance, in the United States, the approved dose is 15 μg three times a week given subcutaneously, whereas in Germany it is 9 µg three times a week (3, 17, 32). To provide more favorable kinetics and subsequent maximal viral suppression, a daily dosing trial was attempted (17, 33, 34). However, in DIRECT trial, a daily dose of 15 µg was found to be associated with discontinuation of CIFN in 21% patients due to various side effects (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, its frequent dosing and similar side effect profile to PEG‐IFN‐α also make compliance challenging. Attempts to create a pegylated version of consensus IFN have been unsuccessful .…”
Section: Clinical Trials Of Alternative Interferons and Immunomodulatmentioning
confidence: 99%
“…CIFN shares an 89, 30, and 60% homology with IFN-α, IFN-β and IFN-ω, respectively (13). CIFN has been shown to be efficacious in HCV genotype 1 patients who have failed therapy with PEG-IFN (14). In order to increase the duration of action, recombinant human CIFN was PEG-modified (pegylated) by Chongqing Fujin Biomedical Co., Ltd. (Chongqing, China).…”
Section: Introductionmentioning
confidence: 99%